The Impact of Generative Artificial Intelligence on Learning Outcomes in Islamic Religious Education in Sweden - Jenny (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The rapid development of Generative Artificial Intelligence (GenAI) has significantly transformed educational practices across various disciplines, including religious education. In Sweden, the integration of digital technologies into education has created opportunities for innovative learning approaches in Islamic Religious Education (IRE). This study aims to examine the impact of Generative Artificial Intelligence on students’ learning outcomes in Islamic Religious Education in Sweden. The research explores how AI-based tools such as ChatGPT, automated learning assistants, and adaptive educational platforms contribute to students’ cognitive understanding, critical thinking, motivation, and engagement in religious learning. Using a qualitative library research approach supported by recent educational and technological studies, this research analyzes the effectiveness of GenAI in facilitating personalized learning, improving access to Islamic educational resources, and enhancing interactive learning experiences. The findings indicate that Generative Artificial Intelligence can positively influence learning outcomes by increasing students’ participation, improving comprehension of Islamic concepts, and supporting independent learning. However, challenges related to ethical concerns, digital literacy, academic integrity, and the accuracy of religious content remain important considerations. The study concludes that the effective implementation of GenAI in Islamic Religious Education requires balanced pedagogical strategies, teacher supervision, and ethical digital frameworks to ensure meaningful and responsible learning experiences.